Nutritional Studies of Rickettsia quintana: Nature of the Hematin Requirement - Myers, William F. (1972)
Rickettsia quintana grew in a liquid medium consisting of a brain-heart infusion base supplemented with starch and hematin. The growth requirement for hematin could not be substituted by compounds of known catalytic activity for H(2)O(2), viz., catalase, potassium pyruvate, or charcoal, or by the reducing compounds sodium sulfite and sodium thioglycollate. R. quintana was catalase-negative, but no H(2)O(2) production could be demonstrated by the catalase-aminotriazole technique. A minimum inoculum giving 10(5) cells/ml was required to initiate growth. The generation time at 33 C was 10 hr. The temperature range for growth was 28 to 37 C. Growth was enhanced when succinate or glutamate was added as energy source.